Development and initial testing of the person-centred health care for older adults survey. - Dow, B.; Fearn, M.; Haralambous, B.; Tinney, J.; Hill, Keith; Gibson, S. (Cambridge University Press, 2013)
Background: Health services are encouraged to adopt a strong person-centered approach to the provision of care and services for older people. The aim of this project was to establish a user-friendly, psychometrically valid, and reliable measure of healthcare staff’s practice, attitudes, and beliefs regarding person-centered healthcare. Methods: Item reduction (factor analysis) of a previously developed “benchmarking person-centred care” survey, followed by psychometric evaluations of the internal consistency reliability and construct validity, was conducted. The initial survey was completed by 1,428 healthcare staff from 17 health services across Victoria, Australia. Results: After removing 17 items from the previously developed “benchmarking person-centred care” survey, the revised 31-item survey (Person-Centred Health Care for Older Adults Survey) attained eight factors that explain 62.7% of the total variance with a Cronbach’s α coefficient of 0.91, indicating excellent internal consistency. Expert consultation confirmed that the revised survey had content validity. Conclusions: The results indicated that the Person-Centred Health Care for Older Adults Survey is a user-friendly, psychometrically valid, and reliable measure of staff perceptions of person-centered healthcare for use in hospital settings.